The coordinators' perception of undergraduate accounting education: an analysis based on the duality of instrumental and substantive reasons (Research, Society and Development, 2020)
Accounting education in Brazil has undergone several changes. Both in the period when it was held in the so-called “trade classes” as well as the moment that it started to be considered a higher education course, several subjects were removed from its curricular matrix that allowed access to knowledge beyond the purely accounting. In this context, this research aims to analyze the preponderance of Instrumental Rationality or Substantial Rationality in the construction of the knowledge of the future accounting professional by the perceptions of the coordinators of the undergraduate course in Accounting Science of a public higher education university, located in the Metropolitan Region of Rio de Janeiro, and the consonance of these with the Pedagogical Project of the course. In order to fulfill the proposed objective, a single case study was used in the unit of analysis, the presential course in Accounting offered by the institution. Data collection was carried out through semi-structured interviews with the coordinators, covering, in general, the curricular matrix used in the course. The collected data were analyzed using the technique called “Discourse of the Collective Subject”. It was found that the subjects of the research consider, in general, instrumental disciplines as being the most relevant for the formation of the future professional of accounting for being more pertinent for the market, a scenario that reflects the primacy of Instrumental Rationality in the scope of the course of Accounting Sciences.